2020
DOI: 10.1007/s10389-020-01391-z
|View full text |Cite
|
Sign up to set email alerts
|

Early school closures can reduce the first-wave of the COVID-19 pandemic development

Abstract: Aim The COVID-19 pandemic presents serious threats to global public health and the world economy. Therefore, the rapid escalation of the number of cases has led to national government and global interventions. This study aimed to assess the effect of school closures on the COVID-19 pandemic and epidemic trajectories in selected countries. Subject and methods Information on the number of cases and population in each country were taken from official government reports. Dates of educational institutions closure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 14 publications
(15 reference statements)
0
43
0
Order By: Relevance
“…Across the world, there are currently more than 1.2 billion children in 186 countries who are affected by school closures due to the pandemic [140]. Most European countries decided to close their schools as early as March 2020 and temporarily reintroduce full-time teaching due to distance learning limitations only as a top-down regulation [141,142].…”
Section: Covid-19 Pandemic and Distance Teaching Realitymentioning
confidence: 99%
“…Across the world, there are currently more than 1.2 billion children in 186 countries who are affected by school closures due to the pandemic [140]. Most European countries decided to close their schools as early as March 2020 and temporarily reintroduce full-time teaching due to distance learning limitations only as a top-down regulation [141,142].…”
Section: Covid-19 Pandemic and Distance Teaching Realitymentioning
confidence: 99%
“…the unit of analysis was national or regional. Of the school closure studies, 13 reported data from a single country or region (the USA (n=10)(14,1921,33,37,42,4749), Italy (n=1)(23), Japan (n=1)(29), and Switzerland (n=1)(43)); four reported discrete estimates for several countries(26,38,44,53); and 15 studies pooled data from multiple countries (globally (n=8)(31,3436,39,46,50,51), Europe only (n=2)(24, 30), Europe and other high income countries (n=5)(15,18,32,40,52)). The studies on school reopening generally reported on single countries (Germany (n=2)(22, 28), USA (n=1)(25), Switzerland (n=1)(43), Belgium (n=1)(27), Israel (n=1)(45), Italy (n=1)(23)), but one reported discrete estimates for three countries (Denamrk, Germany and Norway)(44), two pooled data from multiple countries globally(16, 35), and one pooled data from multiple European countries(24).…”
Section: Resultsmentioning
confidence: 99%
“…Studies that specifically sought to estimate an effect of school closure policy on SARS-CoV-2 transmission included eight school closure studies(14,23,29,32,37,38,42,44), six school reopening studies(22,23,25,28,44,45), and three school holiday studies. The remaining studies primarily sought to estimate the effect of NPIs (but reported an independent estimate for schools, alongside estimates for other NPIs within their analysis).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations